A wideband dual‐polarized magneto‐electric dipole antenna loaded with a disk. Issue 9 (2nd July 2021) - Ren, Yuhui; Li, Ke; Li, Xudong; Jin, Xueyu; Wu, Handong; Wang, Fuwei
Abstract: A novel wideband dual‐polarized antenna with load of a disk is presented in this letter. The antenna is composed of two cross magneto‐electric dipole antennas vertically fixed on an aluminum plate as ground plane, which are excited by two similar Γ‐shaped coaxial feeder. Furthermore, in order to further broaden the impedance bandwidth, a disc‐shaped resonator is loaded on the front end of the dipole. And a metal barrel reflector is loaded around the antenna to further improve the antenna's radiation characteristics. Measured results show that the proposed antenna achieves a 10 dB with bandwidth of 1.2–2.4 GHz, and its port isolation is higher than 28 dB. Moreover, stable radiation pattern with a peak gain of 7.7–9.2 dB is obtained within that band.